FEATURES OF COMMUNICATION OF HUMAN HEALTH AND POVERTY AS A LIFE STYLE - Korobka, Larisa Nikolaevna (Psychological Prospects Journal, 2013)
The article deals with the problem of the method and lifestyle in the system of determinants of health. The social nature of differences in the health of representatives of various social groups is revealed. The influence of poverty as a lifestyle on the state of physical, psychological and psychological health of a person is analyzed.